The Law Enforcement Against The Crime Of Illegal Mining - Keris Aji Wibisono; Umar Ma'ruf (Universitas Islam Sultan Agung, 2021)
This study aims to determine law enforcement against the criminal act of illegal mining in the jurisdiction of the Central Kalimantan Regional Police and the obstacles that arise in law enforcement of the criminal act of illegal mining in the jurisdiction of the Central Kalimantan Regional Police and their solutions. The approach method used is sociological juridical, descriptive analytical research specifications, types and sources of data using primary and secondary data, data collection methods are field studies and literature studies, while the data analysis method uses qualitative analysis. The results of the study indicate that law enforcement for the criminal act of illegal mining in the jurisdiction of the Central Kalimantan Regional Police is carried out through preventive and repressive efforts. Repressive efforts are carried out with outreach activities to the community at the Polres and Polsek levels, while repressive efforts through a series of investigative actions. There are several obstacles in the law enforcement process, namely the presence of irresponsible individuals, limited facilities and infrastructure and a lack of legal awareness from the community.